Growing Older Out of the Closet: A Descriptive Study of Older LGB Persons Living in Lisbon, Portugal. (June 2019) - Pereira, Henrique; de Vries, Brian; Serzedelo, António; Serrano, Juan Pedro; Afonso, Rosa Marina; Esgalhado, Graça; Monteiro, Samuel
There is a paucity of information regarding the needs of older Lesbian, Gay, and Bisexual (LGB) adults in Portugal; to help address this imbalance, this article describes a sample of Portuguese LGB older adults living in the large, urban center of Lisbon. Specifically, the article describes (a) the broad sociodemographic characteristics of LGB 60 years of age or older; (b) the type and level of social support and the nature of interpersonal relationships of these older LGB persons; (c) their physical and sexual health; and (d) the experiences and concerns when accessing social and health-care services, including disclosing their identity to social and health professionals. Across these areas, we further seek to evaluate any differences attributable to gender and compare our results to those in the literature, largely derived from North American studies.